The impact of personalised digital information on the efficiency of vehicle choices in developing countries - Massimo Filippini; Nilkanth Kumar; Suchita Srinivasan (ETH Zurich, CER-ETH - Center of Economic Research, 2024)
Information on operating costs can enable potential buyers to purchase more fuelefficient vehicles. We test this hypothesis with a randomised controlled trial in a developing country, Nepal, using personalised information provision on a unique webbased platform. We find that receiving information on five-year operating cost savings improved the fuel economy of motorcycles that respondents selected on the platform (stated preference), and the models that they actually purchased (revealed preference), compared to receiving fuel economy information. Furthermore, the treatment was particularly effective with respondents who displayed behavioural anomalies. Our study provides novel evidence on the effectiveness of information provision in low-education settings, where the opportunity cost of collecting information may be high.
Keywords: D1; D8; Q4; Q5; 330; Fuel economy; Operating costs; Energy labels; Behavioural anomalies; Randomised informational intervention; Nepal